2021
DOI: 10.3389/fonc.2021.697747
|View full text |Cite
|
Sign up to set email alerts
|

Current Molecular Biology and Therapeutic Strategy Status and Prospects for circRNAs in HBV-Associated Hepatocellular Carcinoma

Abstract: Circular RNAs (circRNAs) are newly classified noncoding RNA (ncRNA) members with a covalently closed continuous loop structure that are involved in immune responses against hepatitis B virus (HBV) infections and play important biological roles in the occurrence and pathogenesis of HCC progression. The roles of circRNAs in HBV-associated HCC (HBV-HCC) have gained increasing attention. Substantial evidence has revealed that both tissue and circulating circRNAs may serve as potential biomarkers for diagnostic, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 171 publications
0
13
0
Order By: Relevance
“…Circular RNAs (circRNAs) are newly classified endogenously expressed regulatory noncoding RNA (ncRNA) members with a single-stranded circular structure that contribute to cell growth, angiogenesis, unlimited replicative potential, and cancer development by sponging different miRNA sequesters (26). Mounting evidence corroborates the fact that circRNAs induce aberrant functions in the HCC tumor microenvironment and mediate tumor biology.…”
Section: Introductionmentioning
confidence: 99%
“…Circular RNAs (circRNAs) are newly classified endogenously expressed regulatory noncoding RNA (ncRNA) members with a single-stranded circular structure that contribute to cell growth, angiogenesis, unlimited replicative potential, and cancer development by sponging different miRNA sequesters (26). Mounting evidence corroborates the fact that circRNAs induce aberrant functions in the HCC tumor microenvironment and mediate tumor biology.…”
Section: Introductionmentioning
confidence: 99%
“…The in silico representation identified a ceRNA network in SARS‐CoV‐infected cells by Arora et al 29 RNA sequencing was carried out by Zhou et al and they discovered a total number of 99 dysregulated circRNAs that were linked to chronic hepatitis B (CHB). The study of the CHB‐related circRNA‐miRNA‐mRNA pathway suggested that TGFb2 was controlled by hsa _circ _0000650 through miR‐6873‐3p sponging 30 . We chose hsa_circ_0004812, which is generated from the ninein‐like (NINL) gene, for further investigation among the circRNAs that have been shown to play a function in infectious illnesses 13 …”
Section: Discussionmentioning
confidence: 99%
“…The study of the CHB-related circRNA-miRNA-mRNA pathway suggested that TGFb2 was controlled by hsa _circ _0000650 through miR-6873-3p sponging. 30 We chose hsa_circ_0004812, which is generated from the ninein-like (NINL) gene, for further investigation among the circRNAs that have been shown to play a function in infectious illnesses. 13 The experimental data showed that hsa_circ_0004812 is significantly overexpressed in symptomatic COVID-19 patients as compared with asymptomatic COVID-19 patients and negative controls.…”
Section: Discussionmentioning
confidence: 99%
“…Non-coding RNAs are aberrantly expressed from the beginning of HBV infection to liver fibrosis/cirrhosis, and finally to HBVrelated HCC. They could participate in the proliferation, apoptosis, epithelial-mesenchymal transition (EMT), invasion, and migration of HCC cells via different mechanisms, such as making impacts on transcriptional regulation in nucleus, protein interactions, alternative splicing, and competing endogenous RNAs, thus affecting tumor progression (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%